Mechanistic lessons learned from studies of planktonic bacteria with metallic nanomaterials: implications for interactions between nanomaterials and biofilm bacteria - Saleh, Navid B.; Chambers, Bryant; Aich, Nirupam; Plazas-Tuttle, Jaime; Phung-Ngoc, Hanh N.; Kirisits, Mary Jo (Frontiers in Microbiology, 2015)
Metal and metal oxide nanoparticles (NPs) are used in numerous applications and have high likelihood of entering engineered and natural environmental systems. Careful assessment of the interaction of these NPs with bacteria, particularly biofilm bacteria, is necessary. This perspective discusses mechanisms of NP interaction with bacteria and identifies challenges in understanding NP-biofilm interaction, considering fundamental material attributes and inherent complexities of biofilm structure. The current literature is reviewed, both for planktonic bacteria and biofilms; future challenges and complexities are identified, both in light of the literature and a dataset on the toxicity of silver NPs toward planktonic and biofilm bacteria. This perspective aims to highlight the complexities in such studies and emphasizes the needs for systematic evaluation of NP-biofilm interaction.